2021
DOI: 10.1109/access.2021.3105727
|View full text |Cite
|
Sign up to set email alerts
|

An Energy-Efficient Hybrid Scheduling Algorithm for Task Scheduling in the Cloud Computing Environments

Abstract: The main intent of the cloud computing to provide utilities to the demands of the users that are booming day by day. To meet the requirements, existing scheduling algorithms focus on the improving the performance and neglecting the energy consumed to fulfill those demands. Hence, we propose a new Hybrid Scheduling Algorithm (HS) which is based on the Genetic Algorithm (GA) and Flower Pollination based Algorithm (FPA) for cloud environments. The proposed scheduling algorithm has surpassed in terms of performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 40 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…The experiment results proved that the proposed technique has the ability to reduce the total execution time, makespan and increase the resource utilization efficiently. It is noteworthy that the FPA algorithm was previously applied for this problem [18]- [20]. However, they differ from our study in the way they adapt and evaluate the generated solutions, as-well-as data-set and different parameters were used.…”
Section: Related Workmentioning
confidence: 90%
“…The experiment results proved that the proposed technique has the ability to reduce the total execution time, makespan and increase the resource utilization efficiently. It is noteworthy that the FPA algorithm was previously applied for this problem [18]- [20]. However, they differ from our study in the way they adapt and evaluate the generated solutions, as-well-as data-set and different parameters were used.…”
Section: Related Workmentioning
confidence: 90%
“…It was implemented on the Cloudsim toolkit and compared over the existing MVO and PSO algorithms and the results revealed that EMVO shows a huge impact over the baseline algorithms by minimizing the makespan while improving the resource utilization. In [ 14 ], the task scheduling algorithm was formulated by the hybridization of the GA and FPA. It was simulated on the Cloudsim toolkit and the addressed parameters were resource utilization, the completion time, and computation cost.…”
Section: Related Workmentioning
confidence: 99%
“…Compared to other methods, it was shown that this technique is able to reduce the value of makespan and give a better convergence speed. Recently, Walia et al 39 presented an energy‐efficient scheduling algorithm (HS) which relies on both FPA and GA algorithms. The aim is to distribute the resources among tasks with less energy.…”
Section: Related Workmentioning
confidence: 99%